2012
DOI: 10.5209/rev_sjop.2012.v15.n1.37334
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Patients who go to a Psychology Clinic Seeking Treatment

Abstract: In order to characterize a typical clinical context, as opposed to an academic or research context, this article will analyze the sociodemographic and clinical characteristics of patients who turn to a psychology clinic in need of professional help. This study was conducted using an initial sample of 1,305 patients at the Universidad Complutense de Madrid (UCM) Clínica Universitaria de Psicología. Of the sociodemographic characteristics studied, it is noteworthy that the majority of patients were women (65%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…Studies of equity of access to IAPT have also tended to focus on more stable patient characteristics such as age, ethnicity and gender; whereas one of the key reviews into equity of therapy use found a wider range of more transient characteristics influential on attendance ( Clarkin and Levy, 2004 ). Indeed, research into non-IAPT psychological therapy has found clinical severity ( Bebbington et al, 2000; Fleury et al, 2012; Simon and Ludman, 2010 ), risk ( Burns et al, 2003; Sales, 2003 ), relationship status ( Briffault et al, 2008; Chen and Rizzo, 2010; Estupiñá et al, 2012 ) and caring responsibilities ( Issakidis and Andrews, 2004 ) among the variables affecting attendance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of equity of access to IAPT have also tended to focus on more stable patient characteristics such as age, ethnicity and gender; whereas one of the key reviews into equity of therapy use found a wider range of more transient characteristics influential on attendance ( Clarkin and Levy, 2004 ). Indeed, research into non-IAPT psychological therapy has found clinical severity ( Bebbington et al, 2000; Fleury et al, 2012; Simon and Ludman, 2010 ), risk ( Burns et al, 2003; Sales, 2003 ), relationship status ( Briffault et al, 2008; Chen and Rizzo, 2010; Estupiñá et al, 2012 ) and caring responsibilities ( Issakidis and Andrews, 2004 ) among the variables affecting attendance.…”
Section: Introductionmentioning
confidence: 99%
“…Outra característica dos atendimentos que pudemos observar foi o predomínio do sexo feminino buscando pelo atendimento, o que corrobora com outros estudos (Fonseca, Fialho, Matos & Figueira, 2013;Estupiña et al, 2012;Pirkis et al, 2011) indicando talvez, entre outras coisas, maior resistência masculina à intervenção ou busca por ajuda psicológica ou ainda maior frequência de problemas emocionais, como a depressão, em mulheres, o que foi uma das nossas maiores queixas e reflete dados de outros estudos (Borooah, 2010).…”
Section: Resultsunclassified
“…O conhecimento das populações que recorrem a tratamento psicológico integra entre outros aspetos a caracterização das determinantes socio-demográficas, de diagnóstico, de fatores de risco na história pessoal e de causas na procura de tratamento (Estupiña, Labrador & García Vera, 2012;Madianos, Zartaloudi, Alevizopoulos & Katostaras, 2011;Pirkis, et al, 2011;Read & Bantall, 2012).…”
unclassified